The Priming Effects of Mirror Visual Feedback on Bilateral Task Practice: A Randomized Controlled Study - Yi-chun Li; Ching-yi Wu; Yu-wei Hsieh; Keh-chung Lin; Grace Yao; Chia-ling Chen; Ya-Yun Lee (Occupational Therapy International, 2019)
The priming effect of mirror visual feedback can be simply provided by inexpensive mirror therapy (MT), which exhibits beneficial effects on sensorimotor recovery in stroke. The present study was a single-blind pretest-posttest study that examined whether the priming effect of mirror visual feedback on bilateral task practice would render better outcomes. Twenty-three patients with chronic stroke were randomized to receive hospital-based task-oriented MT or bilateral arm training (BAT) for 4 weeks at 90 minutes/day, 3 days/week and a home practice for 30-40 minutes/day, 5 days/week. There was the potential trend for MT to improve temperature sense as measured by the revised Nottingham Sensory Assessment (Cohen’s d=1.00; 95% confidence interval, -0.09 to 2.09), and MT increased the Stroke Impact Scale 3.0 total score (d=0.89; 0.003 to 1.71). MT also showed a trend for greater improvements in the Motor Activity Log (amount of use: d=0.62; -0.24 to 1.44; quality of movement: d=0.50; -0.35 to 1.31). MT involving bilateral movement practice with the priming effect of mirror visual feedback may render beneficial effects. The unilateral approach or MT augmented by extra feedback might be appropriate modifications.